Genetic diversity and structure analysis of Croatian garlic collection assessed by SSR markers - Poljuha Danijela; Franić Mario; Kralj Ines; Weber Tim; Šatović Zlatko; Ban Dean; Toth Nina; Dumičić Gvozden; Kereša Snježana; da Cunha Camila Pinto; Goreta Ban Smiljana (Folia Horticulturae, 2021)
This study examines genetic diversity and structure of a Croatian garlic germplasm collection using 13 simple sequence repeat (SSR) markers. A total of 71 alleles were observed across 64 accessions representing 3 Croatian regions (Istria, Dalmatia and continental Croatia) and 16 foreign landraces, with an average of 5.46 alleles per locus. Among the 80 accessions analysed, 61 distinct multilocus genotypes (MLG) were identified, of which 51 represented unique genotypes and the remaining accessions were divided into 10 MLG groups, comprising potential duplicates or redundant genotypes. Model-based Bayesian and hierarchical UPGMA clustering approaches revealed five major groups within the collection which partially correlated with geographical origin. The analysis of molecular variance (AMOVA) showed that the majority (87.71%) of the total molecular diversity is within the Croatian groups of accessions, even though a significant share (12.29%) of diversity derived from genetic diversity among groups. These results support regional structuring, as well as the existence of significant diversity within local populations. This study is the first comprehensive report on an extensive evaluation of genetic resources of garlic maintained by Croatia with the aim of setting the course for future preservation strategies with particular emphasis on the value of diversity in the context of climate change both on macro and micro levels.